THE VERTEBRAL STABILITY. LUMBAR PAIN AND FORMS OF TREATMENT (Cuestiones de Fisioterapia, 2009)
Introduction: all joint is protected by a series of structures: passive, that includes the component ligaments, bony and synovial capsule, among others; and the active ones, formed mainly by the muscles surrounding the joint. A good state of both structures, it is necessary to ensure correct stability of the joint, either static or dynamic. Objectives: pretend to announce the concept of vertebral stability, his relationship with the low back pain and the forms of treatment that the scientific literature offers, to combat the unsteadiness of column. Methodology: it effected a bibliographic re-search in some bases of data of medical scientific evidence-sanitary (Pubmed, The Cochrane Library, Spanish Medical Index), where selected studies related with the subject to treat. We used as key words: low back pain, spine, therapeutic exercise, exercise therapy, motor control. We look for these words in English and Spanish, and we included studies experimental or cause experimental maked since 1990 to 2005. Results and discussion: having a good stability to articulate, is going to prevent muscle-skeletal ailments, which means, as well, to an improvement in the quality of life of the individual. The coordinated training of the superficial muscles of the trunk along with the deep muscles, provides greater stability in the spine and serves as a treatment for improving the symptoms experienced by patients with chronic low back pain. Conclusions: it is necessary that realize more studies that research on the importance of the vertebral stability inside the prevention and treatment of the low back pain.